Attitudes toward hydraulic fracturing: The opposing forces of political conservatism and basic knowledge about fracking. (May 2016) - Choma, Becky L.; Hanoch, Yaniv; Currie, Shannon
Highlights: Political ideology and fracking knowledge tested as predictors of fracking attitudes. Political conservatism and knowledge related to fracking and related attitudes. Ideology and knowledge predicted attitudes in opposing directions. Knowledge moderated relations between ideology and some fracking attitudes. Abstract: Hydraulic fracturing has become a contentious issue around the globe. In the present study, using a sample of American adults ( n = 412), the role of political orientation (conservative vs. liberal) and basic knowledge about fracking on fracking risk perception attitudes, fracking economic attitudes, energy reliance attitudes, trust of energy information sources, and preferred dwelling distance from energy operations was investigated. Basic knowledge about hydraulic fracturing as a possible moderating mechanism was also explored. Correlational and regression results revealed that political ideology and basic fracking knowledge are key predictors of fracking and energy source attitudes, and that the nature of the relation between ideology and fracking risk perceptions, fracking economic attitudes, reliance on natural gas, wind and solar, and distrust of government agencies, are influenced by an individual's basic knowledge about fracking.